2023
DOI: 10.1002/jbio.202200375
|View full text |Cite
|
Sign up to set email alerts
|

Neural network‐based optimization of sub‐diffuse reflectance spectroscopy for improved parameter prediction and efficient data collection

Abstract: In this study, a general and systematical investigation of sub‐diffuse reflectance spectroscopy is implemented. A Gegenbauer‐kernel phase function‐based Monte Carlo is adopted to describe photon transport more efficiently. To improve the computational efficiency and accuracy, two neural network algorithms, namely, back propagation neural network and radial basis function neural network are utilized to predict the absorption coefficient μnormala, reduced scattering coefficient μnormals′ and sub‐diffusive quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…demonstrated recovery of μa and μs with mean relative error ranging from 1.62% to 5.92% and 0.8% to 1.6%, respectively, with their baseline neural network and its physics-guided variants but only for a simulation dataset. An et al 24 . developed ANNs for their spectroscopy system, which predicted μa with mean absolute error ranging from 0.13 to 0.17 cm1 and μs ranging from 1.43 to 1.71 cm1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated recovery of μa and μs with mean relative error ranging from 1.62% to 5.92% and 0.8% to 1.6%, respectively, with their baseline neural network and its physics-guided variants but only for a simulation dataset. An et al 24 . developed ANNs for their spectroscopy system, which predicted μa with mean absolute error ranging from 0.13 to 0.17 cm1 and μs ranging from 1.43 to 1.71 cm1.…”
Section: Discussionmentioning
confidence: 99%
“…An et al. 24 developed ANNs for their spectroscopy system, which predicted with mean absolute error ranging from 0.13 to and ranging from 1.43 to . However, their ANN prediction was limited to only four wavelengths compared to our broad-spectrum prediction ranging from 500 to 740 nm.…”
Section: Discussionmentioning
confidence: 99%
“…Chong et al demonstrated recovery of μ a and μ’ with mean relative error ranging from 1.62-5.92% and 0.8-1.6%, respectively, with their baseline neural network and its physics-guided variants for a simulated dataset[20]. An et al developed ANNs for their four-wavelength spectroscopy system, which predicted μ a with mean absolute error ranging from 0.13-0.17 cm -1 and μ s ′ ranging from 1.43-1.71 cm -1 [21]. Lan et al predicted μ a with Euclidean distance = 0.25 and μ s ′ with Euclidean distance = 4.14[13].…”
Section: Discussionmentioning
confidence: 99%
“…These techniques leverage the inherent capacity of ML models to learn complex patterns and relationships from large datasets, enabling accurate predictions and analysis of optical properties. In the aspect of measuring technique, compared to ours, the existing ML-based models deal with different DRS techniques, such as frequency domain DRS (FD-DRS) that estimates optical properties from measuring amplitude and phase shift of the diffusely reflected light [11][12][13][14], or spatially resolved DRS [15][16][17], or subdiffusive reflectance in which measurements are made closer than MFP and therefore more optical properties are involved (first similarity parameter W) [17,18]. The generic DRS, which is the technique we work with, compared to FD-DRS, requires less expensive devices, less complicated experimental setups, and the data interpretation is a lot easier due to the simpler mechanism.…”
Section: Introductionmentioning
confidence: 99%